Segmented and unequal: evidence on the dual labor market and youth unemployment from the Korea youth survey. (3rd July 2022) - Hong, Yoonpyo; Lee, Kyungeun
ABSTRACT: Empirical studies of the dual labor market, particularly those employing the endogenous switching regression model, are rare, and few studies appear to have considered youth unemployment, which may have negative long-term effects on economic growth and social equality. Using data from South Korea, we test the proposition that the dual structure of the labor market is one of the main causes that make the youth unemployment rate higher and worsens social inequality. The results strongly support the labor market hypothesis, suggesting that the dual market model is more relevant for the youth labor market; the findings also indicate that the social inequality structure may be strengthened by the dual market structure that excludes youth with socially disadvantaged conditions from the primary labor market.